Pengambilan Keputusan Dalam Organisasi - Fathoni, Wildan; Asiah, Nur; Asikin, Nur; S, Sukatin; Qarnain, Zul (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Decision making is a fundamental process in every organization, directly influencing its direction, performance, and achievement of goals. This article discusses the basic concepts of decision making, its stages, and the classification of decisions into strategic, tactical, and operational levels. It also explores psychological factors that affect the decision-making process, such as individual values, personality, risk-taking tendencies, emotions, cognitive biases, experience, mindset, perception, motivation, attitudes, and stress. The research method used is library research with a qualitative approach, analyzing secondary data from various reliable sources. The discussion is enriched with an Islamic perspective on decision making, emphasizing the importance of deliberation (musyawarah), moral values, and spirituality in the process. With a comprehensive understanding of the concepts, factors, and methods of decision making, it is expected that leaders and members of organizations will be able to make effective, responsible decisions that provide optimal benefits for both the organization and society.